An ultra-sensitive UHPLC-MS/MS assay for the quantification of orally administered vancomycin in plasma - Sauter, Max; Uhl, Philipp; Foerster, Kathrin; Mohr, Isabelle; Hoene, Rahel Thangam; Merle, Uta; Burhenne, Jürgen; Haefeli, Walter E. (Journal of pharmaceutical and biomedical analysis, 2019)
Though marketed for over half a century, little is known about the pharmacokinetics of oral vancomycin except that its bioavailability is low, thus making accurate determination of plasma concentrations difficult. To quantify plasma concentrations of vancomycin after oral administration, we developed an ultra-sensitive UHPLC-MS/MS assay and validated it according to FDA´s and EMA´s pertinent guidelines. A fast and simple protein precipitation method followed by short UHPLC chromatography was developed for extraction and separation of vancomycin from plasma. Quantification was performed via heated positive electrospray tandem mass spectrometry with multiple reaction monitoring using deuterated internal standard. The assay was linear in the calibrated concentration range of 0.05-100ng/mL showing correlation coefficients >0.997. Intraday and interday accuracy showed coefficients of variation <12% at the lower limit of quantification (LLOQ) of 0.05ng/mL and <6% in the calibrated range while corresponding values for precision were <13% and <8%, respectively. With its high sensitivity, the assay allows for the accurate quantification of therapeutic plasma concentrations in the therapeutic range (up to 100μg/mL) in 1000-fold diluted samples with a sample volume decreased down to 1μL. The UHPLC-MS/MS assay was successfully used for the determination of trough plasma concentrations of two patients with Clostridium difficile infection receiving oral vancomycin therapy and its performance was compared to a commercial immunoassay for concentrations close to its LLOQ.
Gesehen am 02.09.2019